Solid-state electrolyte and method for producing the same, solid-state battery cell, battery device, power-using device
Patent Information
- Application Number
- CN202510424593.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]根据本申请实施例,对A3SbS4型硫化物固态电解质采用阴、阳离子共同掺杂的方式,使用具有更高氧化电位的-2价和/或-1价的阴离子对固态电解质进行阴离子掺杂,具有更高氧化电位的-2价和/或-1价的阴离子在掺杂取代部分S2-阴离子后,可以减少固态电解质中的阴离子在正极侧的氧化,使其具有更高的电压稳定性和高的电化学稳定性;同时采用+6价和/或+7价的阳离子进行掺杂可以减少阳离子在负极侧被还原而进一步提高固态电解质的高电压稳定性,并且通过+6价和/或+7价阳离子的掺杂取代部分Sb5+,可以在固态电解质中引入更多的活性离子(Na+或Li+)空位,进而可以提升固态电解质的离子电导率。本申请实施例通过选用特定的阴离子和阳离子对A3SbS4型硫化物固态电解质进行共同掺杂,可以使A3SbS4型硫化物固态电解质具有更高的电压稳定性和电化学稳定窗口,同时固态电解质可以具有更高的离子电导率,可以使固态电解质匹配高电压体系的活性材料,提升电池单体的循环性能。
Smart Images

Figure CN122931010A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, specifically to a solid electrolyte and its preparation method, a solid battery cell, a battery device, and an electrical device. Background Technology
[0002] Batteries are widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric cars, electric airplanes, electric ships, electric car toys, electric toy ships, electric toy airplanes, and power tools.
[0003] In the development of battery cells, improving the cycle performance of battery cells is one of the urgent problems to be solved. Summary of the Invention
[0004] To address the aforementioned technical problems, this application provides a solid electrolyte and its preparation method, a solid battery cell, a battery device, and an electrical device.
[0005] In a first aspect, embodiments of this application provide a solid electrolyte, the general formula of which is A. 3-(m-5)α-γ Sb 1-α M α S 4-β-γ X β Y γ In the formula, A is Li or Na; M includes one or more cations with a valence of +m, where m is 6 or 7; X includes one or more anions with a valence of -2; Y includes one or more anions with a valence of -1, and the standard oxidation potentials of X and Y ions are greater than S. 2- The standard oxidation potentials are: 0 < α < 1, 0 ≤ β, 0 ≤ γ, 0 < β + γ < 4, 0 < α + γ < 3.
[0006] According to embodiments of this application, the A3SbS4 type sulfide solid electrolyte is co-doped with anions and cations. Anions with higher oxidation potential (-2 and / or -1 valence) are used to anion-dopat the solid electrolyte. These anions, with higher oxidation potential, substitute for S in the doped portion. 2- Adding anions reduces the oxidation of anions on the positive electrode side of the solid electrolyte, resulting in higher voltage and electrochemical stability. Simultaneously, doping with +6 and / or +7 valent cations reduces the reduction of cations on the negative electrode side, further enhancing the high voltage stability of the solid electrolyte. Furthermore, the doping with +6 and / or +7 valent cations replaces some of the Sb. 5+ More active ions (Na+) can be introduced into the solid electrolyte. + Or Li +Vacancies can be created, thereby improving the ionic conductivity of the solid electrolyte. In this application, specific anions and cations are selected to co-dope the A3SbS4 type sulfide solid electrolyte, resulting in higher voltage stability and an electrochemical stability window. Simultaneously, the solid electrolyte exhibits higher ionic conductivity, allowing it to be matched with active materials in high-voltage systems and improving the cycle performance of individual battery cells.
[0007] In some embodiments, 0.01 ≤ α ≤ 0.15.
[0008] In some embodiments, 0.05 ≤ β + γ ≤ 0.5.
[0009] In some embodiments, M includes one or more of W, Mo, Cr, Mn, Se, Te, Re, and Os.
[0010] In some embodiments, X includes one or more of O, Se, and Te.
[0011] In some embodiments, Y includes one or more of F, Cl, Br, I, BH4, BF4, SCN, and OCN.
[0012] In some embodiments, the ionic conductivity of the solid electrolyte is 0.1 mS / cm-100 mS / cm.
[0013] In some embodiments, the electronic conductivity of the solid electrolyte is 1 × 10⁻⁶. -6 mS / cm-1×10 -3 mS / cm.
[0014] Secondly, embodiments of this application provide a method for preparing a solid electrolyte, comprising the following steps:
[0015] According to chemical formula A 3-(m-5)α-γ Sb 1-α M α S 4-β-γ X β Y γ It provides precursors comprising source A, source Sb, source M, elemental sulfur, source X, and source Y; wherein A is Li or Na, M includes one or more cations with a valence of +m, where m is 6 or 7; X includes one or more anions with a valence of -2, and Y includes one or more anions with a valence of -1, and the standard oxidation potential S of X and Y ions is given. 2- The standard oxidation potentials are: 0 < α < 1, 0 ≤ β, 0 ≤ γ, 0 < β + γ < 4, 0 < α + γ < 3.
[0016] The raw materials are ground and mixed in an inert atmosphere to obtain a premix.
[0017] The premixed material is annealed to obtain a solid electrolyte.
[0018] In some embodiments, the grinding process takes 1-48 hours.
[0019] In some embodiments, the grinding speed is 200 rpm to 1000 rpm.
[0020] In some embodiments, the annealing temperature is 450°C-650°C.
[0021] In some embodiments, the heating rate of the annealing treatment is 0.5℃ / min to 5℃ / min.
[0022] In some embodiments, the holding time for the annealing treatment is 5h-30h.
[0023] Thirdly, embodiments of this application provide a solid-state battery cell, which includes a solid electrolyte from the first aspect of this application or a solid electrolyte obtained by the preparation method according to the second aspect of this application.
[0024] In some embodiments, a solid-state battery cell includes a positive electrode, a negative electrode, and a solid electrolyte membrane, wherein the solid electrolyte membrane is located between the positive electrode and the negative electrode, and the solid electrolyte membrane includes the solid electrolyte.
[0025] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer located on at least one side of the positive current collector, the positive electrode film layer including the solid electrolyte.
[0026] In some embodiments, the mass percentage of the solid electrolyte in the positive electrode film is 5%-50% based on the total mass of the positive electrode film.
[0027] Fourthly, embodiments of this application provide a battery device, including a solid-state battery cell according to the third aspect of this application.
[0028] Fifthly, embodiments of this application provide an electrical device, including a solid-state battery cell according to the third aspect of this application or a battery device according to the fourth aspect of this application. Attached Figure Description
[0029] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the embodiments of this application will be briefly described below. Obviously, the drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on the drawings without creative effort.
[0030] Figure 1 The diagram shows the structural features of a vehicle provided in some embodiments of this application.
[0031] Figure 2 This is an exploded schematic diagram of a battery provided for some embodiments of this application.
[0032] Figure 3 for Figure 2 The diagram shows an exploded view of the battery module.
[0033] Figure 4 The X-ray diffraction (XRD) patterns of the solid electrolytes provided in Example 1 and Comparative Example 4 of this application are shown.
[0034] Figure 5 This is a graph showing the cyclic voltammetry test results of the solid electrolyte provided in Example 1 of this application.
[0035] The accompanying drawings are not necessarily drawn to scale.
[0036] The reference numerals in the attached drawings are explained as follows: 1. Vehicle; 2. Battery unit; 3. Controller; 4. Motor; 5. Housing; 5a. First housing section; 5b. Second housing section; 5c. Reception space; 6. Battery module; 7. Battery cell. Detailed Implementation
[0037] The following detailed description, with appropriate reference to the accompanying drawings, specifically discloses embodiments of the battery cell, battery device, and power-consuming device of this application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.
[0038] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0039] Unless otherwise specified, all embodiments and optional embodiments of this application may be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure of this application.
[0040] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions, and such technical solutions shall be deemed to be included in the disclosure of this application.
[0041] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0042] Unless otherwise specified, in this application, the terms "first," "second," etc., are used to distinguish different objects, rather than to describe a specific order or primary / secondary relationship.
[0043] In this application, the terms "multiple" or "various" refer to two or more kinds.
[0044] In the description of the embodiments of this application, unless otherwise specified, "above" or "below" the second feature can mean that the first feature is in direct contact with the second feature, or that the first feature is in indirect contact with the second feature through an intermediate medium. Furthermore, "above," "over," and "on top" can mean that the first feature is directly above or diagonally above the second feature, or simply that the first feature is at a higher horizontal level than the second feature. "Below," "below," and "under" the second feature can mean that the first feature is directly below or diagonally below the second feature, or simply that the first feature is at a lower horizontal level than the second feature.
[0045] Unless otherwise stated, the terms used in this application have the common meanings as commonly understood by those skilled in the art.
[0046] Unless otherwise stated, the values of the parameters mentioned in this application can be determined using various testing methods commonly used in the art, for example, according to the testing methods given in the embodiments of this application. Unless otherwise stated, the test temperature for each parameter is 25°C.
[0047] The battery device mentioned in the embodiments of this application can be a single physical module comprising one or more battery cells to provide higher voltage and capacity. For example, the battery mentioned in this application can include battery cells, battery modules, or battery packs.
[0048] A single battery cell is the smallest unit that makes up a battery, and it can independently perform the functions of charging and discharging. When there are multiple battery cells, they are connected in series, parallel, or mixed connections through a busbar.
[0049] In some embodiments, the battery device may be a battery module; when there are multiple battery cells, the multiple battery cells are arranged and fixed to form a battery module.
[0050] In some embodiments, the battery device may be a battery pack, which includes a housing and individual battery cells, with the individual battery cells or battery modules housed within the housing.
[0051] In some embodiments, the housing may be part of the vehicle's chassis structure. For example, a portion of the housing may be at least a part of the vehicle's floor, or a portion of the housing may be at least a part of the vehicle's crossbeams and longitudinal beams.
[0052] In some embodiments, the battery device may be an energy storage device. Energy storage devices include energy storage containers, energy storage cabinets, etc.
[0053] The technical solutions described in the embodiments of this application are applicable to battery devices and electrical devices that use battery devices.
[0054] Battery devices can be used as the power source for electrical devices or as energy storage units for electrical devices. Electrical devices can be, but are not limited to, mobile devices (such as mobile phones, tablets, laptops, etc.), vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0055] Electrical devices can choose the type of battery device according to their usage needs, such as individual battery cells, battery modules, or battery packs.
[0056] For ease of explanation, the following embodiments will use a vehicle as an example of an electrical device.
[0057] Figure 1 The diagram shows the structural features of a vehicle provided in some embodiments of this application.
[0058] like Figure 1 As shown, a battery device 2 is installed inside the vehicle 1. The battery device 2 can be located at the bottom, front, or rear of the vehicle 1. The battery device 2 can be used to power the vehicle 1; for example, the battery device 2 can serve as the operating power source for the vehicle 1.
[0059] The vehicle 1 may also include a controller 3 and a motor 4. The controller 3 is used to control the battery device 2 to supply power to the motor 4, for example, for the power needs of the vehicle 1 during starting, navigation and driving.
[0060] In some embodiments, the battery device 2 can not only serve as the operating power source for the vehicle 1, but also as the driving power source for the vehicle 1, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1.
[0061] Figure 2 This is a schematic diagram of a battery explosion provided for some embodiments of this application. For example... Figure 2 As shown, the battery device 2 includes a housing 5 and battery cells (not shown), with the battery cells housed within the housing 5.
[0062] The housing 5 is used to house individual battery cells, and the housing 5 can have various structures. In some embodiments, the housing 5 may include a first housing portion 5a and a second housing portion 5b, which overlap each other, and together define a housing space 5c for housing the individual battery cells. The second housing portion 5b may be a hollow structure with one end open, and the first housing portion 5a may be a plate-like structure, with the first housing portion 5a covering the open side of the second housing portion 5b to form a housing 5 with the housing space 5c; alternatively, both the first housing portion 5a and the second housing portion 5b may be hollow structures with one side open, with the open side of the first housing portion 5a covering the open side of the second housing portion 5b to form a housing 5 with the housing space 5c. Of course, the first housing portion 5a and the second housing portion 5b can have various shapes, such as cylinders, cuboids, etc.
[0063] To improve the sealing performance after the first housing part 5a and the second housing part 5b are connected, a sealing element, such as sealant or sealing ring, can also be provided between the first housing part 5a and the second housing part 5b.
[0064] Assuming that the first box section 5a covers the top of the second box section 5b, the first box section 5a can also be called the upper box cover, and the second box section 5b can also be called the lower box.
[0065] In battery device 2, there can be one or more battery cells. If there are multiple battery cells, they can be connected in series, in parallel, or in a mixed configuration. A mixed configuration means that multiple battery cells are connected in both series and parallel configurations. Multiple battery cells can be directly connected in series, in parallel, or in a mixed configuration, and then the whole assembly of multiple battery cells is housed in housing 5. Alternatively, multiple battery cells can first be connected in series, in parallel, or in a mixed configuration to form battery module 6, and then multiple battery modules 6 can be connected in series, in parallel, or in a mixed configuration to form a whole assembly, which is then housed in housing 5.
[0066] Figure 3 for Figure 2 The diagram shows an exploded view of the battery module.
[0067] like Figure 3 As shown, in some embodiments, there are multiple battery cells 7, which are first connected in series, parallel, or mixed to form a battery module 6. The multiple battery modules 6 are then connected in series, parallel, or mixed to form a whole and housed in a casing.
[0068] Multiple battery cells 7 in battery module 6 can be electrically connected through a busbar component to achieve parallel, series, or mixed connection of multiple battery cells 7 in battery module 6.
[0069] The battery cells mentioned in the embodiments of this application may include lithium-ion battery cells or sodium-ion battery cells.
[0070] Solid-state battery cells are battery cells that use solid electrolytes as electrolyte materials. Solid-state battery cells typically include a casing and an electrode assembly located inside the casing. The electrode assembly generally includes a positive electrode, a negative electrode, and a solid electrolyte membrane. The solid electrolyte membrane is located between the positive and negative electrode and plays the role of isolating the positive and negative electrodes and transporting active ions. The solid electrolyte membrane includes the solid electrolyte.
[0071] A3SbS4 (A is Li or Na) type sulfide solid electrolytes have high ionic conductivity and air stability, but the sulfur content in their composition... 2- Anions are easily oxidized on the positive electrode side, while Sb 5+ The cations are easily reduced on the negative electrode side, resulting in poor high-voltage stability and a very narrow electrochemical stability window for A3SbS4 type sulfide solid electrolytes. This makes them unsuitable as active materials in high-voltage systems, limiting their application in solid-state battery cells. Therefore, improving the high-voltage stability and extending the electrochemical stability window of A3SbS4 type sulfide solid electrolytes is one of the urgent problems to be solved.
[0072] In view of this, embodiments of this application provide a negative electrode-free solid-state battery cell, which, by adjusting the composition design of the solid electrolyte, has high voltage stability and a wide electrochemical stability window.
[0073] [Solid electrolyte]
[0074] One embodiment of this application provides a solid electrolyte, the general formula of which is A. 3-(m-5)α-γ Sb 1-α M α S 4-β-γ X β Y γ In the formula, A is Li or Na; M includes one or more cations with a valence of +m, where m is 6 or 7; X includes one or more anions with a valence of -2; Y includes one or more anions with a valence of -1, and the standard oxidation potentials of X and Y ions are greater than S. 2- The standard oxidation potentials are: 0 < α < 1, 0 ≤ β, 0 ≤ γ, 0 < β + γ < 4, 0 < α + γ < 3.
[0075] According to embodiments of this application, the A3SbS4 type sulfide solid electrolyte is co-doped with anions and cations. Anions with higher oxidation potential (-2 and / or -1 valence) are used to anion-dopat the solid electrolyte. These anions, with higher oxidation potential, substitute for S in the doped portion. 2-Adding anions reduces the oxidation of anions on the positive electrode side of the solid electrolyte, resulting in higher voltage and electrochemical stability. Simultaneously, doping with +6 and / or +7 valent cations reduces the reduction of cations on the negative electrode side, further enhancing the high voltage stability of the solid electrolyte. Furthermore, the doping with +6 and / or +7 valent cations replaces some of the Sb. 5+ More active ions (Na+) can be introduced into the solid electrolyte. + Or Li + Vacancies can be created, thereby increasing the ionic conductivity of solid electrolytes.
[0076] In this embodiment of the application, by selecting specific anions and cations to co-dope the A3SbS4 type sulfide solid electrolyte, the A3SbS4 type sulfide solid electrolyte can have higher voltage stability and electrochemical stability window, and the solid electrolyte can be matched with the active materials of high voltage system, thereby improving the cycle life of the battery cell.
[0077] In some embodiments, M may include W(W) 6+ ), Mo (Mo 6+ ), Cr (Cr 6+ Mn(Mn) 6+ Mn 7+ ), Se(Se 6+ ),Te(Te 6+ ), Re(Re 6+ Re 7+ ), Os(Os 6+ One or more of the following.
[0078] According to the embodiments of this application, the above-mentioned elements, as cation doping elements, can introduce active ion vacancies into the solid electrolyte, while further reducing the reduction reaction of cations on the negative electrode side, thereby improving the ionic conductivity of the solid electrolyte and giving it high voltage stability.
[0079] In some embodiments, α can satisfy 0.01≤α≤0.15. As an example, α can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or any range of the above values.
[0080] According to the embodiments of this application, by keeping the molar amount of cation doping in the solid electrolyte within the above-mentioned range, it is beneficial to enable the solid electrolyte to have high voltage stability and introduce more active ion vacancies to improve its ionic conductivity. At the same time, the solid electrolyte can have high structural stability, which is beneficial to enable the solid battery cell to achieve both high rate performance and improved cycle performance.
[0081] In some embodiments, X may include O(O 2- ), Se(Se 2- ),Te(Te 2- One or more of the following.
[0082] In some embodiments, Y may include F(F - ), Cl(Cl - ), Br(Br) - ), I(I - ), BH4 (BH4) - ), BF4 (BF4) - ), SCN (SCN) - ), OCN (OCN) - One or more of the following.
[0083] It is understandable that the same element can have different valence states in different states, and compounds with different valence states can be selected as doping materials according to the doping position of the element.
[0084] According to embodiments of this application, the aforementioned -2 and -1 valence anionic elements are used as doping elements, and they have a higher S content than S. 2- The oxidation potential of ions can reduce the oxidation reaction of anions on the positive electrode side in solid electrolytes, giving solid electrolytes high voltage stability, which is beneficial to improving their electrochemical stability window, and thus improving the rate performance and cycle performance of battery cells.
[0085] In some embodiments, β and γ can satisfy 0.05 ≤ β + γ ≤ 0.5. As an example, β + γ can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.15, 0.20, 0.25, 0.30, 0.35, 0.40, 0.45, 0.50, or any range of the above values.
[0086] According to the embodiments of this application, by keeping the molar percentage of doped anions in the solid electrolyte within the above-mentioned range, the solid electrolyte can have high voltage stability and a wide electrochemical stability window. At the same time, the solid electrolyte can have high structural stability, which is beneficial for the battery cell to achieve both high rate performance and improved cycle performance.
[0087] In some embodiments, the ionic conductivity of the solid electrolyte can be between 1 mS / cm and 100 mS / cm. As an example, the ionic conductivity of the solid electrolyte can be 1 mS / cm, 5 mS / cm, 10 mS / cm, 15 mS / cm, 20 mS / cm, 25 mS / cm, 30 mS / cm, 35 mS / cm, 40 mS / cm, 45 mS / cm, 50 mS / cm, 55 mS / cm, 60 mS / cm, 65 mS / cm, 70 mS / cm, 75 mS / cm, 80 mS / cm, 85 mS / cm, 90 mS / cm, 95 mS / cm, 100 mS / cm, or any range of the above values. Optionally, the ionic conductivity of the solid electrolyte can be between 10 mS / cm and 80 mS / cm.
[0088] In some embodiments, the electronic conductivity of the solid electrolyte can be 1×10⁻⁶. -6 mS / cm to 1×10 -3 mS / cm. As an example, the electronic conductivity of a solid electrolyte can be 1 × 10⁻⁶ mS / cm. -6 mS / cm, 1×10 -5 mS / cm, 1×10 -4 mS / cm, 1×10 -3 mS / cm, or any range of the above values.
[0089] In some embodiments, the solid electrolyte may include Na. 2.8 Sb 0.9 W 0.1 S 3.8 O 0.1 F 0.1 Na 2.9 Sb 0.95 W 0.05 S 3.9 O 0.05 F 0.05 Na 2.9 Sb 0.9 W 0.1 S 3.95 O 0.05 Na 2.9 Sb 0.9 W 0.1 S 3.9 O 0.1 One or more of them.
[0090] In this application, the chemical composition and crystal structure of the solid electrolyte can be determined by methods known in the art. For example, the elemental composition of the solid electrolyte can be confirmed by measuring and analyzing the cross-sectional area of the solid electrolyte membrane using scanning electron microscopy (SEM) and combining it with energy dispersive spectroscopy (EDS), X-ray diffraction (XRD) analysis, etc.
[0091] In this application, the ionic conductivity of the solid electrolyte has a well-known meaning in the art and can be measured using methods and instruments known in the art. For example, electrochemical impedance spectroscopy can be used. A certain amount (e.g., 120 mg) of solid electrolyte is placed in a mold and pressed under a certain pressure (e.g., 360 MPa) to form a lithium metal symmetric battery. The blocking electrode can be a carbon electrode. The ionic conductivity is tested and calculated. The test frequency range can be 0.1 Hz to 1 MHz, and the amplitude can be 10 mV.
[0092] In this application, the electronic conductivity of the solid electrolyte has a well-known meaning in the art and can be measured using methods and instruments known in the art. For example, a certain amount (e.g., 120 mg) of solid electrolyte can be placed in a mold, pressed and shaped under a certain pressure (e.g., 360 MPa) for DC polarization testing. The polarization voltage can be 150 mV. The electronic conductivity can be measured and calculated by testing the current change over 12 hours.
[0093] In this application, the electrochemical stability range of the solid electrolyte has a meaning known in the art and can be determined using methods and instruments known in the art. For example, a positive electrode composite can be obtained by mixing a solid electrolyte and a binder in a certain mass ratio, and then assembled with an alloy negative electrode (such as Na3Sn) to form a mold battery. Cyclic voltammetry tests can be performed in the 0-5V voltage range at a scan rate of 0.1mV / s.
[0094] In this application, the above parameters of the solid electrolyte can be tested directly by taking the solid electrolyte or by taking samples from the solid battery cell.
[0095] When the test sample is obtained from a solid-state battery cell, as an example, the sampling can be performed according to the following steps: Discharge the solid-state battery cell (generally to a fully discharged state), remove the solid electrolyte membrane after disassembling the battery cell, clean the solid electrolyte membrane with a non-polar solvent (such as n-heptane, cyclohexane, etc.) and soak it for a certain time (e.g., 2-10 hours); then remove the solid electrolyte membrane and dry it at a certain temperature and time (e.g., 100°C, 4 hours), remove the solid electrolyte membrane after drying; bake the dried solid electrolyte membrane at a certain temperature and time (e.g., 300°C, 2 hours), select a region of the baked solid electrolyte membrane and sample the solid electrolyte (sampling can be done by scraping powder with a blade); sieve the collected solid electrolyte (e.g., sieve with a 200-mesh sieve), and finally obtain a solid electrolyte membrane sample that can be used to test the material parameters mentioned above in this application.
[0096] In some embodiments, the solid electrolyte membrane may also be different from one or more of the types of sulfide solid electrolytes, oxide solid electrolytes, halide solid electrolytes and organic solid electrolytes described above.
[0097] Sulfide solid electrolytes have high 10 -2 S / cm to 10 -3 A lithium-ion conductivity of S / cm facilitates the formation of contact interfaces between electrodes and exhibits high mechanical strength and flexibility. In this application embodiment, there are no particular limitations on the type of sulfide-based solid electrolyte, and all known sulfide materials used in the battery field are acceptable. Sulfide-based solid electrolytes may include Li6PS5Cl (LPSCl), Thio-LISICON (Li... 3.25 Ge 0.25 P 0.75 S4), Li2S-P2S5-LiCl, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, Li3PS4, Li7P3S 11 , LiI-Li2S-B2S3, Li3PO4-Li2S-Si2S, Li3PO4-Li2S-SiS2, LiPO4-Li2S-SiS, Li 10 GeP2S 12 Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 and Li7P3S 11 One or more of them.
[0098] Oxide-based solid electrolytes exhibit high safety in air and have a 10 -3 S / cm to 10 -4 The lithium-ion conductivity (S / cm) is lower than that of sulfide-based solid electrolytes, but relatively higher. Furthermore, oxide-based solid electrolytes exhibit high electrochemical safety and mechanical strength. However, oxide-based solid electrolytes have high oxidation voltage. Additionally, solid electrolytes have high grain boundary resistance, making it difficult to form a contact interface between the electrode and electrolyte, requiring high-temperature heat treatment processes of 1000°C or higher, and these processes are difficult to scale up. In the embodiments of this application, the oxide-based solid electrolyte can be any known oxide material used in the field of lithium batteries. In the embodiments of this application, the oxide-based solid electrolyte includes perovskite solid electrolyte, sodium superionic conductor solid electrolyte (NASICON), lithium superionic conductor solid electrolyte (LISICON), and lithium lanthanum zirconium oxide solid electrolyte (LLZO).
[0099] Organic solid electrolytes (OSEs) are a type of solid electrolyte. OSEs can readily form electrode interfaces and minimize dendrite growth, thus ensuring stable reactions between OSEs and lithium metal. The disadvantages of OSEs are their relatively low lithium-ion conductivity and the fact that they typically require high-temperature operation. In this embodiment, the OSE comprises polyethylene oxide (PEO).
[0100] The thickness of the solid electrolyte membrane can be selected differently depending on the properties of the desired all-solid-state battery. Specifically, in some embodiments, the thickness of the solid electrolyte membrane can be from 0.1 μm to 1000 μm; in other embodiments, the thickness of the solid electrolyte membrane can be from 1 μm to 500 μm; in still other embodiments, the thickness of the solid electrolyte membrane can be from 20 μm to 30 μm; this application does not limit it in this regard.
[0101] [Preparation methods of solid electrolytes]
[0102] Another embodiment of this application provides a method for preparing a solid electrolyte, comprising the following steps:
[0103] S100, according to chemical formula A 3-(m-5)α-γ Sb 1-α M α S 4-β-γ X β Y γIt provides precursors comprising source A, source Sb, source M, elemental sulfur, source X, and source Y; wherein A is Li or Na, M includes one or more cations with a valence of +m, where m is 6 or 7; X includes one or more anions with a valence of -2, and Y includes one or more anions with a valence of -1, and the standard oxidation potential S of X and Y ions is given. 2- The standard oxidation potentials are: 0 < α < 1, 0 ≤ β, 0 ≤ γ, 0 < β + γ < 4, 0 < α + γ < 3.
[0104] S200: The raw materials are ground and mixed in an inert atmosphere to obtain a premix.
[0105] S300 involves annealing the premixed material to obtain a solid electrolyte.
[0106] According to the embodiments of this application, by mixing, grinding, and calcining the raw materials of each element according to the specified ratio, anions and cations are introduced into the sulfide solid electrolyte for doping. The introduced anion and cation doping can reduce the oxidation / reduction reactions of the solid electrolyte on the positive / negative electrode side, improve the high voltage stability of the solid electrolyte, and give the solid electrolyte a high electrochemical stability window. Therefore, the above preparation method can be used to prepare the solid electrolyte provided in the embodiments of this application, and the prepared solid electrolyte can have all the physicochemical properties of the solid electrolyte provided in the embodiments of this application.
[0107] Elemental sulfur, used as an oxidant and sulfur supplement in the preparation of solid electrolytes, is prone to melting or even volatilization at high temperatures during direct calcination. This loss of oxidant and sulfur during preparation can prevent other raw materials from reacting completely. Furthermore, at high temperatures, elemental sulfur may react with other cations, resulting in impurities in the final product and a decline in the performance of the prepared solid electrolyte. The solid electrolyte preparation method provided in this application pre-processes the mixture of raw materials containing elemental sulfur through grinding and mixing before high-temperature calcination. This allows the elemental sulfur to pre-react with other raw materials during low-temperature grinding and mixing, forming a chemical anchor, thereby reducing the loss of sulfur during subsequent high-temperature calcination, reducing impurities in the final product, and improving the electrochemical performance of the product.
[0108] In some embodiments, the grinding process can be 1 hour to 48 hours. For example, the grinding process can be 1 hour, 2 hours, 5 hours, 8 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours, 48 hours, or any range of the above values. Optionally, the grinding process can be 5 hours to 40 hours.
[0109] According to the embodiments of this application, by keeping the grinding time of each raw material within the above-mentioned range, elemental sulfur can be fully chemically bonded to other raw materials, reducing the loss of sulfur elements during high-temperature calcination.
[0110] In some embodiments, the grinding speed can be between 200 rpm and 1000 rpm. For example, the grinding speed can be 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm, 800 rpm, 850 rpm, 900 rpm, 950 rpm, 1000 rpm, or any range of the above values. Optionally, the grinding speed can be between 400 rpm and 800 rpm.
[0111] According to the embodiments of this application, by keeping the grinding speed of each raw material within the above-mentioned range, elemental sulfur can be fully mixed and contacted with other raw materials, which is beneficial for elemental sulfur to undergo sufficient pre-reaction with other raw materials. At the same time, the grinding speed within the above-mentioned range can provide a suitable temperature, reducing the volatilization loss of elemental sulfur during the grinding process.
[0112] In some embodiments, the annealing temperature can be between 450°C and 650°C. For example, the annealing temperature can be 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, or any range of the above values.
[0113] In some embodiments, the heating rate of the annealing treatment can be 0.5℃ / min to 5℃ / min. As an example, the heating rate of the annealing treatment can be 0.5℃ / min, 0.6℃ / min, 0.7℃ / min, 0.8℃ / min, 0.9℃ / min, 1.0℃ / min, 1.5℃ / min, 2.0℃ / min, 2.5℃ / min, 3.0℃ / min, 3.5℃ / min, 4.0℃ / min, 4.5℃ / min, 5.0℃ / min, or any range of the above values.
[0114] In some embodiments, the holding time for annealing can be 5h-30h. As an example, the holding time for annealing can be 5h, 8h, 10h, 12h, 5h, 18h, 20h, 2h, 25h, 28h, 30h, or any range of the above values.
[0115] It is understandable that elemental sulfur can be used as a sulfur source for preparing solid electrolytes. However, this application does not limit all sulfur in the preparation of solid electrolytes to elemental sulfur. Sulfur can also be derived from other raw material elements, and these other elements can exist in the form of compounds with sulfur.
[0116] In the embodiments of this application, in the step of providing the elemental raw materials for preparing the solid electrolyte, the raw materials and their proportions can be determined according to the chemical formula of the solid electrolyte.
[0117] Source A can be a lithium source or a sodium source. As an example, the lithium source can include one or more of Li₂S, Li₂O, Li₂CO₃, and elemental Li; the Na source can include one or more of Na₂S, Na₂O, Na₂CO₃, and elemental Na.
[0118] The M source material may include one or more compounds containing the element M, which includes one or more of W, Mo, Cr, Mn, Se, Te, Re, and Os. As an example, the M source material may include one or more of elemental W, WS2, WS3, elemental Mo, MoS2, and MoS3.
[0119] Sb source materials may include one or more of Sb2S3, Sb2S3, and Sb2S5.
[0120] The X source material may include one or more compounds containing the element X, where X includes one or more of O, Se, and Te. For example, the X source material may include one or more of Sb₂O₅, WO₃, and Na₂O.
[0121] Y-source materials may include one or more compounds containing the element Y, where Y includes one or more of F, Cl, Br, I, BH4, BF4, SCN, and OCN. As an example, Y-source materials may include one or more of NaF, NaCl, and NaBF4.
[0122] [Positive electrode plate]
[0123] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer located on at least one side of the current collector, the positive electrode film layer including a positive active material.
[0124] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the current collector.
[0125] In some embodiments, the positive electrode active material may include one or more of lithium phosphate, layered lithium transition metal oxide, Prussian blue compounds, polyanionic compounds, and sodium transition metal oxide.
[0126] If the positive electrode active material is one or more of lithium phosphate and layered lithium transition metal oxide, then the positive electrode active material can be used in lithium-ion battery cells; if the positive electrode active material is one or more of Prussian blue compounds, polyanionic compounds, and sodium transition metal oxide, then the positive electrode material can be used in sodium-ion battery cells.
[0127] Lithium-containing phosphates may include one or more of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, and their respective modified compounds.
[0128] Examples of layered lithium-containing transition metal oxides may include one or more of lithium cobalt oxides, lithium nickel oxides, lithium manganese oxides, lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides, lithium nickel cobalt aluminum oxides, and their respective modified compounds.
[0129] In some embodiments, the layered lithium-containing transition metal oxide may include Ni. The molar amount of Ni may account for more than 70% of the total molar amount of transition metal elements in the layered lithium-containing transition metal oxide; optionally, the molar amount of Ni may account for more than 80% of the total molar amount of transition metal elements in the layered lithium-containing transition metal oxide; more preferably, the molar amount of Ni may account for more than 90% of the total molar amount of transition metal elements in the layered lithium-containing transition metal oxide.
[0130] The higher the Ni content in layered lithium-containing transition metal oxides, the higher the energy density of the battery cell.
[0131] In some embodiments, layered lithium-containing transition metal oxides may include Li a Ni b Co c M d O e A f Wherein, 0 < a ≤ 1.2; 0.8 ≤ b < 1; 0 < c < 1; 0 < d < 1; b + c + d = 1; 1 ≤ e ≤ 2; 0 ≤ f ≤ 1; M includes, but is not limited to, one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, and B; A includes, but is not limited to, one or more of N, F, S, and Cl. This can further improve the energy density of individual battery cells.
[0132] In some embodiments, as an example, layered lithium-containing transition metal oxides may include, but are not limited to, LiNi. 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.8 Co 0.15 Al 0.05O2, LiNi 0.9 Co 0.06 Mn 0.04 O2, LiNi 0.92 Co 0.06 Mn 0.02 O2, LiNi 0.96 Co 0.02 Mn 0.02 O2, LiNi 0.96 Co 0.02 Mn 0.02 O2N 0.02 One or more of them.
[0133] During the charging and discharging process of a battery cell, Li undergoes insertion / extraction and consumption, resulting in varying molar Li content at different discharge states. In the examples of positive electrode active materials in this application, the molar Li content refers to the initial state of the material, i.e., the state before feeding. After charge-discharge cycles, the molar Li content may change when the positive electrode active material is applied to the battery cell.
[0134] In some embodiments, as an example, sodium transition metal oxides may include, but are not limited to:
[0135] Na 1-x Cu h Fe k Mn l M 1 m O 2-y M 1 It is one or more of Li, Be, B, Mg, Al, K, Ca, Ti, Co, Ni, Zn, Ga, Sr, Y, Nb, Mo, In, Sn, and Ba, 0 <x≤0.33,0<h≤0.24,0≤k≤0.32,0<l≤0.68,0≤m<0.1,h+k+l+m=1,0≤y<0.2;
[0136] Na 0.67 Mn 0.7 Ni z M 2 0.3-z O2, where M 2 It is one or more of Li, Mg, Al, Ca, Ti, Fe, Cu, Zn and Ba, 0 <z≤0.1;
[0137] Na a Li b Ni c Mn d Fe e O2, of which 0.67 <a≤1,0<b<0.2,0<c<0.3,
[0138] 0.67<d+e<0.8, b+c+d+e=1.
[0139] In some embodiments, by way of example, the polyanionic compound may include, but is not limited to:
[0140] A 1 f M 3 g (PO4) i O j X 1 3-j , where A is one or more of H, Li, Na, K and NH4, M 3 is one or more of Ti, Cr, Mn, Fe, Co, Ni, V, Cu and Zn, X 1 is one or more of F, Cl and Br, 0<f≤4, 0<g≤2, 1≤i≤3, 0≤j≤2;
[0141] Na n M 4 PO4X 2 , where M 4 is one or more of Mn, Fe, Co, Ni, Cu and Zn, X 2 is one or more of F, Cl and Br, 0<n≤2;
[0142] Na p M 5 q (SO4)3, where M 5 is one or more of Mn, Fe, Co, Ni, Cu and Zn, 0<p≤2, 0<q≤2;
[0143] Na s Mn t Fe 3-t (PO4)2(P2O7), where 0<s≤4, 0≤t≤3, for example t is 0, 1, 1.5, 2 or 3.
[0144] In some embodiments, by way of example, the Prussian blue-based compound may include, but is not limited to:
[0145] A u M 6 v [M 7 (CN)6] w ·xH2O, where A is H + , NH4 + , one or more of alkali metal cations and alkaline earth metal cations, M 6 and M 7are each independently one or more of transition metal cations, 0<u≤2, 0<v≤1, 0<w≤1, 0<x<6. For example, A is H + , Li + , Na + , K + , NH4 + , Rb + , Cs + , Fr + , Be 2+ , Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ and Ra 2+ , one or more of them, M 6 and M 7 are each independently a cation of one or more transition metal elements selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sn and W. Optionally, A is one or more of Li + , Na + and K + , M 6 is a cation of one or more transition metal elements selected from Mn, Fe, Co, Ni and Cu, and M 7 is a cation of one or more transition metal elements selected from Mn, Fe, Co, Ni and Cu.
[0146] In the enumeration of the positive electrode active material in the embodiments of the present application, the molar content of O is only a theoretical state value, and the oxygen release from the crystal lattice will cause the molar content of O to change, so that the actual molar content of O will fluctuate.
[0147] The modified compound of each of the above positive electrode active materials may be obtained by doping modification and / or surface coating modification of the positive electrode active material.
[0148] In some embodiments, the positive electrode film layer may optionally further include a binder. By way of example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.
[0149] In some implementations, the weight percentage of the binder in the positive electrode film layer is greater than or equal to 0.5%, which is beneficial to obtaining good adhesive performance.
[0150] In some embodiments, the positive electrode film layer further includes a conductive agent. By way of example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0151] In some embodiments, the positive electrode film layer further includes a solid electrolyte.
[0152] Solid electrolytes may include any one of the solid electrolytes provided in the embodiments of this application or a combination thereof.
[0153] In some embodiments, based on the total mass of the positive electrode film, the mass percentage of solid electrolyte in the positive electrode film can be 5%-50%, for example, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, or any range of the above values.
[0154] In some embodiments, the current collector serving as the positive electrode may also be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be made by forming a metal material, such as aluminum, aluminum alloy, copper, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, on the polymer material substrate. The polymer material substrate may include polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), and other substrates.
[0155] In some embodiments, the thickness of the positive current collector is from 4 μm to 20 μm. It is optionally from 6 μm to 18 μm, and more preferably from 8 μm to 16 μm.
[0156] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto a current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0157] [Negative electrode plate]
[0158] The negative electrode includes a negative current collector and a negative electrode film layer located on at least one side of the negative current collector. The negative electrode film layer may include a negative electrode active material.
[0159] As an example, the negative electrode active material may include one or more of the following: artificial graphite, natural graphite, mesophase micro carbon spheres, hard carbon, soft carbon, silicon, and silicon-carbon composites.
[0160] Silicon-based composite materials can be prepared by methods known in the art. For example, they can be prepared by vapor deposition using graphite and silicon materials as raw materials.
[0161] In some embodiments, the negative electrode active material may further include one or more of Li, Sn, Zn and their alloys.
[0162] In some embodiments, the negative electrode film layer may further include a negative electrode conductive agent. As an example, the negative electrode conductive agent may include, but is not limited to, one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0163] In some embodiments, the negative electrode film layer may also include other additives. As an example, other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc.
[0164] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. Examples of metal foils include copper foil, copper alloy foil, aluminum foil, and aluminum alloy foil. The composite current collector may include a polymeric material substrate and a metal material layer formed on at least one side of the polymeric material substrate. Examples of metal materials include, but are not limited to, one or more of copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. Examples of polymeric material substrates include, but are not limited to, one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0165] The negative electrode sheet does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode sheet may also include a conductive undercoat layer sandwiched between the negative electrode current collector and the negative electrode film layer and located on the surface of the negative electrode current collector, which may be composed of a conductive agent and a binder; in some embodiments, the negative electrode sheet may also include a protective layer covering the surface of the negative electrode film layer.
[0166] In some embodiments, the battery cell can be a negative electrode-free battery cell, in which case no negative electrode film layer containing a negative electrode active material layer is disposed on the negative electrode current collector. When the battery cell is a negative electrode-free battery cell, a functional layer for depositing lithium metal can be disposed on the surface of the negative electrode current collector. The material of the functional layer can include a metallic material, such as an elemental metal or an alloy. The type of metallic material can be any type known in the art that can serve as a negative electrode functional layer in a negative electrode-free battery cell, and this application does not limit this.
[0167] Example
[0168] The following embodiments describe the disclosure of this application in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of the disclosure of this application. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.
[0169] Example 1
[0170] solid electrolyte
[0171] Sodium source, Sb source, W source, elemental S, O source and F source were added to a ball mill jar in a certain ratio, with a ball-to-material ratio of 30:1. The mixture was ball-milled at 600 rpm for 36 hours, with a 1-minute pause every 10 minutes during the ball milling process to obtain a premix.
[0172] The premix was compacted under 360 MPa pressure, heated to 550 °C at a heating rate of 3 °C / min under an argon atmosphere, held at that temperature for 24 h, and then naturally cooled to room temperature to obtain the solid electrolyte Na. 2.8 Sb 0.9 W 0.1 S 3.8 O 0.1 F 0.1 .
[0173] Positive electrode powder
[0174] NaNi, the positive electrode active material 0.33 Fe 0.33 Mn 0.33 O2, the solid electrolyte and carbon nanofibers (VGCF) prepared above are mixed and ground evenly in a mass ratio of 67:30:3 to obtain positive electrode powder.
[0175] Anode powder
[0176] Metallic Na and metallic Sn are mixed in a molar ratio of 3:1 and heated to 500℃, held for 5 minutes, and then naturally cooled to room temperature to obtain Na3Sn alloy. The Na3Sn alloy is then ground into powder to obtain negative electrode powder.
[0177] Solid-state battery cells
[0178] The solid electrolyte prepared above is added into the mold battery sleeve and pre-pressed under a pressure of 100MPa to form a solid electrolyte membrane. Then, positive electrode powder and negative electrode powder are respectively covered on both sides of the solid electrolyte membrane to form a three-layer structure of positive electrode-solid electrolyte membrane-negative electrode. The three-layer structure is compacted together using a pressure of 360MPa. Stainless steel pillars are connected to the positive electrode and negative electrode as current collectors to obtain a solid battery cell.
[0179] Examples 2-7
[0180] The preparation method of the solid-state battery cell is similar to that in Example 1. The difference lies in the different composition parameters of the solid electrolyte. For details of parameter adjustments, please refer to Table 1.
[0181] Examples 8-13
[0182] The preparation method of the solid-state battery cell is similar to that in Example 1. The difference lies in the preparation parameters of the solid electrolyte. The specific parameter adjustments are shown in Table 1.
[0183] Comparative Examples 1-3
[0184] The preparation method of the solid-state battery cell is similar to that in Example 1. The difference lies in the different composition parameters of the solid electrolyte. For details of parameter adjustments, please refer to Table 1.
[0185] Comparative Example 4
[0186] The preparation method of the solid-state battery cell is similar to that in Example 1, except that the composition method of the solid electrolyte is different. The specific preparation method is as follows:
[0187] Sodium, Sb, W, elemental S, O, and F sources were mixed uniformly in a specified ratio to obtain a premix. The premix was compacted under 360 MPa pressure and heated to 550 °C at a heating rate of 3 °C / min under an argon atmosphere, held at that temperature for 24 h, and then naturally cooled to room temperature to obtain a solid electrolyte. The chemical composition of the solid electrolyte is represented as Na. 2.8 Sb 0.9 W 0.1 S 3.8 O 0.1 F 0.1 .
[0188] Test section
[0189] 1. Ionic conductivity of solid electrolytes
[0190] Solid electrolyte was placed in a mold and pressed into shape at 360 MPa and 550 °C. A symmetrical cell was assembled using carbon powder as a blocking electrode according to the structure of "blocking electrode-solid electrolyte-blocking electrode". Electrochemical impedance spectroscopy was performed, and the ionic conductivity was calculated. The test frequency range was 0.1 Hz-1 MHz, and the amplitude was 10 mV. The impedance R of the solid electrolyte was obtained according to the formula: The ionic conductivity of the solid electrolyte can be calculated, where L is the thickness of the solid electrolyte membrane and S is the cross-sectional area of the solid electrolyte membrane.
[0191] 2. Electronic conductivity of solid electrolytes
[0192] Solid electrolyte was placed in a mold and pressed into shape at 360 MPa and 550 °C. A symmetrical cell was assembled using carbon powder as the electrode according to an "electrode-solid electrolyte-electrode" structure, maintaining an external pressure of 360 MPa. Using an electrochemical workstation, the polarization voltage was set to 150 mV for 12 hours. The final stable current value I was recorded. The formula calculates the electronic conductivity of the solid electrolyte, where L is the thickness of the solid electrolyte film, S is the cross-sectional area of the solid electrolyte film, and U is the constant voltage applied to the battery.
[0193] 3. Electrochemical stability range
[0194] Solid electrolyte and VGCF were mixed uniformly at a mass ratio of 9:1 to obtain a positive electrode composite. Na3Sn was used as the negative electrode to assemble a mold battery. Cyclic voltammetry tests were performed in the voltage range of 0 to 5 V at a scan rate of 0.1 mV / s to obtain the electrochemical stability range of the solid electrolyte.
[0195] 4. Electrochemical performance of solid-state battery cells
[0196] At 25°C, the solid-state battery cell was charged to 3.6V at a constant current of 0.1C and the charging capacity D0 was recorded; after standing for 10 minutes, it was discharged to 2V at a constant current of 0.1C and the discharge capacity C0 was recorded; the solid-state battery cell was charged and discharged according to the above scheme, and the discharge capacity of the nth cycle was recorded as Cn.
[0197] The ratio of the first-cycle discharge capacity C0 of a solid-state battery cell to the positive electrode active material is used as the first-cycle discharge capacity (mAh / g) of the solid-state battery cell.
[0198] The first charge-discharge efficiency (%) of a solid-state battery cell = C0 / D0 × 100%;
[0199] n-cycle capacity retention rate (%) = Cn / C0 × 100%.
[0200] The test results are detailed in Table 1.
[0201]
[0202] Figure 4 The image shows the XRD patterns of the final product in Example 1, the premix in Example 1, and the final product in Example 4. It can be seen that the solid electrolyte prepared in Example 1 has the same crystal structure as the cubic phase Na3SbS4, and there are no obvious impurity peaks in the XRD pattern. This indicates that W... 6+ O 2- and F - Elements were successfully doped into the Na3SbS4 bulk phase; however, a significant WS2 peak appeared in the solid electrolyte prepared in Comparative Example 4. This indicates that during the direct high-temperature calcination preparation of the solid electrolyte, sulfur reacted with the doping element, resulting in side reaction products in the prepared solid electrolyte and affecting its purity.
[0203] Figure 5 The cyclic voltammetry test spectrum of the solid electrolyte prepared in Example 1 of this application is shown. It can be seen from the figure that an oxidation peak appears at about 2.8V in the first cycle of the cyclic voltammetry test, and a reduction peak appears at about 1V. The electrochemical stability range of the material is 1V-2.8V. Furthermore, the oxidation and reduction peaks disappear in the second cycle. It is inferred that the solid electrolyte may be passivated, which enhances the electrochemical stability of the solid electrolyte.
[0204] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A solid-state battery cell, characterized in that, It includes a positive electrode, a negative electrode, and a solid electrolyte membrane, wherein the solid electrolyte membrane is located between the positive electrode and the negative electrode, and the solid electrolyte membrane includes a solid electrolyte; The general formula of the solid electrolyte is A 3-(m-5)α-γ Sb 1-α M α S 4-β-γ X β Y γ In the formula, A is either Li or Na; M includes one or more cations with a valence of +m, where m is 6 or 7; X includes one or more anionic elements with a valence of -2, and Y includes one or more anionic elements with a valence of -1, and the standard oxidation potentials of X ions and Y ions are greater than S. 2- Standard oxidation potential; 0<α<1, 0≤β, 0≤γ, 0<β+γ<4, 0<α+γ<3.
2. The solid-state battery cell according to claim 1, characterized in that, 0.01≤α≤0.15。 3. The solid-state battery cell according to claim 1 or 2, characterized in that, 0.05≤β+γ≤0.
5.
4. The solid-state battery cell according to any one of claims 1-3, characterized in that, M includes one or more of W, Mo, Cr, Mn, Se, Te, Re, and Os.
5. The solid-state battery cell according to any one of claims 1-4, characterized in that, X includes one or more of O, Se, and Te.
6. The solid-state battery cell according to any one of claims 1-5, characterized in that, Y includes one or more of F, Cl, Br, I, BH4, BF4, SCN, and OCN.
7. The solid-state battery cell according to any one of claims 1-6, characterized in that, The ionic conductivity of the solid electrolyte is 0.1 mS / cm-100 mS / cm; and / or The electronic conductivity of the solid electrolyte is 1×10⁻⁶. -6 mS / cm-1×10 -3 mS / cm.
8. The solid-state battery cell according to any one of claims 1-7, characterized in that, The positive electrode includes a positive current collector and a positive electrode film layer located on at least one side of the positive current collector, the positive electrode film layer including the solid electrolyte.
9. The solid-state battery cell according to claim 8, characterized in that, Based on the total mass of the positive electrode film, the mass percentage of the solid electrolyte in the positive electrode film is 5%-50%.
10. A battery device, characterized in that, Includes any one of the solid-state battery cells according to claims 1-9.
11. An electrical appliance, characterized in that, Includes the solid-state battery cell according to any one of claims 1-9 or the battery device according to claim 10.
12. A solid electrolyte, characterized in that, The general formula for the solid electrolyte is: A 3-(m-5)α-γ Sb 1-α M α S 4-β-γ X β Y γ In the formula, A is either Li or Na. M includes one or more cations with a valence of +m, where m is 6 or 7; X includes one or more anionic elements with a valence of -2, and Y includes one or more anionic elements with a valence of -1, and the standard oxidation potential S of X ions and Y ions is... 2- Standard oxidation potential; 0<α<1, 0≤β, 0≤γ, 0<β+γ<4, 0<α+γ<3.
13. A method for preparing a solid electrolyte, characterized in that, Includes the following steps: According to chemical formula A 3-(m-5)α-γ Sb 1-α M α S 4-β-γ X β Y γ It provides precursors comprising source A, source Sb, source M, elemental sulfur, source X, and source Y; wherein A is Li or Na, M includes one or more cations with a valence of +m, where m is 6 or 7; X includes one or more anions with a valence of -2, and Y includes one or more anions with a valence of -1, and the standard oxidation potential S of X and Y ions is given. 2- Standard oxidation potential; 0<α<1, 0≤β, 0≤γ, 0<β+γ<4, 0<α+γ<3; The raw materials are ground and mixed in an inert atmosphere to obtain a premix. The premixed material is annealed to obtain a solid electrolyte.
14. The preparation method according to claim 13, characterized in that, The grinding process takes 1-48 hours; and / or The grinding speed is 200rpm-1000rpm.
15. The preparation method according to claim 13 or 14, characterized in that, The annealing temperature is 450℃-650℃; and / or The annealing process has a heating rate of 0.5℃ / min to 5℃ / min; and / or The holding time for the annealing treatment is 5h-30h.